2006
DOI: 10.1375/twin.9.6.933
|View full text |Cite
|
Sign up to set email alerts
|

The Southern California Twin Register at the University of Southern California: II

Abstract: The Southern California Twin Register was initiated in 1984 at the University of Southern California, and continues to grow. This article provides an update of the register since it was described in the 2002 special issue of this journal. The register has expanded considerably in the past 4 years, primarily as a result of recent access to Los Angeles County birth records and voter registration databases. Currently, this register contains nearly 5000 twin pairs, the majority of whom are school age. The potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The details of the protocol can be found in Baker et al (2006). Briefly, the visit included behavioral interviews, neurocognitive testing, social risk factor assessment, and psychophysiological recording of the twins.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the protocol can be found in Baker et al (2006). Briefly, the visit included behavioral interviews, neurocognitive testing, social risk factor assessment, and psychophysiological recording of the twins.…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensive assessment of each child was made, including cognitive, behavioral, psychosocial, and psycho-physiological measures based on individual testing and interviews of the child and primary caregiver during the laboratory visit, with additional teacher surveys completed and returned by mail. A detailed description of the study, including a summary of the measures, can be found in Baker, Barton, Lozano, Raine, and Fowler (2006).…”
Section: Overview Of the Usc Twin Study Of Risk Factors For Antisociamentioning
confidence: 99%
See 1 more Smart Citation
“…During Wave I (2001Wave I ( -2004) the twins were 9-10 years old (mean age = 9.60, SD = 0.59); during Wave II (2003II ( -2006) the twins were 11-13 years old (mean age = 11.79, SD = 0.92); during Wave III (2006-2010) the twins were 14-16 years old (mean age = 14.87, SD = 0.87); and during Wave 4 (2008-2011) the twins were 17-18 years old (mean age = 17.28, SD = 0.77). The total study sample includes 1,562 subjects, including 169 monozygotic (MZ) male, 171 MZ female, 121 dizygotic (DZ) male, 120 DZ female, and 200 DZ opposite-sex twin pairs (Baker et al 2006). The present study used data from Wave 2, as information on nutrients was not collected during Wave 1.…”
Section: Participantsmentioning
confidence: 99%
“…When both questionnaire and DNA results were available, there was a 90 % agreement between the two. Complete details on the procedures and measures can be found elsewhere (Baker et al 2006). …”
Section: Participantsmentioning
confidence: 99%